Prevalence of subclinical mastitis and determination of risk factors in goats milked manually and mechanized in herds of Comondú, Baja California Sur, Mexico - Ávalos Castro, Raúl; Palomares Resendiz, Gabriela; Díaz Aparicio, Efrén; Medina Córdova, Noé de Jesús (Acta Universitaria, 2022)
In order to determine the prevalence of subclinical mastitis, pathogens that cause it, and risk factors in manual and mechanical milking of goats in Comondú, Baja California Sur, Mexico, 12 farms were evaluated. A total of 234 milk samples were taken from 117 goats, 90 from mechanized milking and 144 from manual milking. The prevalence of subclinical mastitis was 52% (95% CI: 44%-60%), being 86% (95% CI: 78%-94%) in manual milking and 33% (95% CI: 19%–47%) in mechanized milking. The most prevalent groups of pathogens were coagulase negative Staphylococcus and Staphylococcus aureus. The chances of mastitis increase in goats milked manually, those with poor hygiene in pens, and those older than five years (OR: 33.30).